Optimization of cutting parameters for CO2 laser beam cutting using variable wiight grey-taguchi method - Khairul Fikri, Muhammad (2011)
Carbon Dioxide (CO2) laser beam cutting (LBC) process involves several parameters. These parameters need to be optimized in order to get the best quality output. Researchers had applied various types of optimization methods which are used for single or multi-objectives problems. One of the methods is Grey-Taguchi method. However, there is a disadvantage of these methods. This study focuses on improving the Grey-Taguchi method in order to optimize machining parameters for CO2 LBC. The Variable Weight Grey-Taguchi method is proposed which considering all possible weights to be assigned to the control and noise factors. The considered control factors are stand-off distance, cutting speed and laser power. This study also considers surrounding temperature as noise factor. The superior of these methods is merely depending on the response factors which are Surface Roughness (SR), Kerf Taper Angle (TAP), Heat Affected Zone (HAZ) and Kerf Width (KW). Results from Matlab assisted physical experiment shows there is an effect on weight assigning to the factors. Results also show that the proposed method successfull improved all the response factors. Surface roughness had improved by 49.4%, taper 52%, Heat Affected Zone (HAZ) 9.3% and kerf width 46.2%. As conclusion, this study had successfully proposed an improved optimization method for LBC process.